2004
DOI: 10.1083/jcb.200404150
|View full text |Cite
|
Sign up to set email alerts
|

A novel phosphatidylinositol(3,4,5)P3 pathway in fission yeast

Abstract: The mammalian tumor suppressor, phosphatase and tensin homologue deleted on chromosome 10 (PTEN), inhibits cell growth and survival by dephosphorylating phosphatidylinositol-(3,4,5)-trisphosphate (PI[3,4,5]P3). We have found a homologue of PTEN in the fission yeast, Schizosaccharomyces pombe (ptn1). This was an unexpected finding because yeast (S. pombe and Saccharomyces cerevisiae) lack the class I phosphoinositide 3-kinases that generate PI(3,4,5)P3 in higher eukaryotes. Indeed, PI(3,4,5)P3 has not been dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 32 publications
5
55
0
1
Order By: Relevance
“…These phenotypes are similar to those observed in class E Vps mutants such sst4/vps27Á and sst6Á. 39) In addition, Pxa1p is required for recycling of Vps10p from the endosome to the Golgi compartment (Fig. 3C).…”
Section: Discussionsupporting
confidence: 62%
“…These phenotypes are similar to those observed in class E Vps mutants such sst4/vps27Á and sst6Á. 39) In addition, Pxa1p is required for recycling of Vps10p from the endosome to the Golgi compartment (Fig. 3C).…”
Section: Discussionsupporting
confidence: 62%
“…3D) and tested its binding with lipids spotted on a nitrocellulose membrane. Compared with the positive 6His-Ksg1(PH) (Mitra et al, 2004) and negative 6His-mEGFP controls, we found that 6His-Mid1(PH) interacts with several lipids (Fig. 3E).…”
Section: The Ph Domain Of Mid1 Directly Interacts With Lipidsmentioning
confidence: 93%
“…The source of the remaining PtdIns(3,4,5)P 3 is currently unknown, but PikH, an unusual PI3-kinase with a PH-domain, is unlikely to be responsible, as a sextuple mutant with this gene also knockedout, has a similar residual level of PtdIns(3,4,5)P 3 (unpublished observation). We hypothesize that, as in fission yeast, a metabolic pathway starting from PtdIns(3)P, generated by PikE, the Dictyostelium homologue of Vps34, may be responsible (Mitra et al, 2004).…”
Section: Discussionmentioning
confidence: 99%